A Prognostic Index to Identify the Risk of Developing Depression Symptoms Among U.S. Medical Students Derived From a National, Four-Year Longitudinal Study. (February 2019) - Dyrbye, Liselotte N.; Wittlin, Natalie M.; Hardeman, Rachel R.; Yeazel, Mark; Herrin, Jeph; Dovidio, John F.; Burke, Sara E.; Cunningham, Brooke; Phelan, Sean M.; Shanafelt, Tait D.; van Ryn, Michelle
Abstract : Purpose: To determine baseline individual and school-related factors associated with increased risk of developing depression symptoms by year four (Y4) of medical school, and to develop a prognostic index that stratifies risk of developing depression symptoms (Depression-PI) among medical students. Method: The authors analyzed data from 3, 743 students (79% of 4, 732) attending 49 U.S. medical schools who completed baseline (2010) and Y4 (2014) surveys. Surveys included validated scales measuring depression, stress, coping, and social support. The authors collected demographics and school characteristics and conducted multivariate analysis to identify baseline factors independently associated with Y4 depression symptoms. They used these factors to create a prognostic index for developing depression. They randomly divided the data into discovery (n = 2, 455) and replication (n = 1, 288) datasets and calculated c statistics ( c ). Results: The authors identified eight independent prognostic factors for experiencing depression symptoms during training within the discovery dataset: age; race; ethnicity; tuition; and baseline depression symptoms, stress, coping behaviors, and social support. The Depression-PI stratified four risk groups. Compared with the low risk group, those in the intermediate, high, and very high risk groups had an odds ratio of developing depression of, respectively, 1.75, 3.98, and 9.19 ( c = 0.71). The replication dataset confirmed the risk groups. Conclusions: Demographics; tuition; and baseline depression symptoms, stress, coping behaviors, and social support are independently associated with risk of developing depression during training among U.S. medical students. By stratifying students into four risk groups, the Depression-PI may allow for a tiered primary prevention approach. Abstract : Supplemental Digital Content is available in the text.